Pengaruh Kualitas Produk, Fitur Produk dan Promosi Terhadap Keputusan Pembelian Daihatsu Gran Max dengan Brand Image Sebagai Variabel Moderasi - Muharom, Mumuh; Yulia, Iis Anisa; Mulia, Agus Prana (Jurnal EMT KITA, 2024)
This research aims to analyze the influence of product quality, product features and promotion on purchasing decisions for the Daihatsu Gran Max with brand image as a moderating variable. The sample used in this research was 200 respondents. Data was collected using a purposive sampling method and hypothesis testing using Moderated Regression Analysis (MRA). The results of this research show that Product Quality has a significant influence on Purchasing Decisions, Product Features have a significant influence on Purchasing Decisions and Promotion has a significant influence on Purchasing Decisions, Brand Image can moderate the influence of Product Quality, Product Features and Promotion on Purchasing Decisions.